Substitution of finishing feed with yellow corn in creole chickens - Paredes, Manuel (2023)
The aim of this study was to evaluate five levels of substitution of the finishing feed with yellow corn in the diet of Creole chickens and their effect on productive performance. In total, 96 improved 70-day-old male Creole chickens were randomly distributed in 6 treatments, each with 4 replicates of 4 birds. The chickens received diets with 0 (control diet), 20, 40, 60, 80 and 100% yellow corn in substitution of the finisher feed. The chickens of the 0, 20 and 40% treatments, in the phase of 70 to 112 days of age, obtained higher body weight gain and better feed conversion. Chicken carcass yield decreased with 40, 60, 80, and 100% substitution with yellow corn in the diet. The carcass contained less abdominal fat and liver weight with the 0, 20 and 40% treatments. In conclusion, the finishing feed for Creole chickens could be substituted up to 40% by yellow corn without affecting body weight, and up to 20% without decreasing carcass yield.